Government Control, Uncertainty, and Investment Decisions in China's Listed Companies - Liping Xu; Jingwei Wang; Yu Xin (China Journal of Accounting Research, 2010)
This paper empirically investigates the relation between uncertainty and investment among China's listed companies, and analyzes the influence of government control on the investment-uncertainty relation. We find that there is a negative relation between total firm uncertainty and investment in China's listed companies. However, this holds only for privately controlled firms. Among privately controlled listed firms, investment is negatively related to firm-specific uncertainty, whereas among government-controlled ones, investment is positively related to market uncertainty. We also find that the risk-taking preference of government-controlled listed companies is greater among those firms with fewer investment opportunities. Finally, among financially distressed firms, the negative relation between investment and uncertainty becomes nonsignificant because of risk shifting, which is more serious among government-controlled listed companies. We conclude that government control leads to state interference and weak corporate governance, which, in turn, distorts investment decision making among listed companies.